An analysis of student development strategies in schools under the secondary educational service area office Chiang Mai - Prasartyingyod, Jirayut; Intanon, Tiptida; Thongchaloem, Phasakorn (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2025)
This research aims to: 1) analyze strategies for student development, 2) examine the alignment of vision, identity, and student development strategies, and 3) provide recommendations for formulating student development strategies for schools under the Secondary Education Service Area Office Chiang Mai. This qualitative research utilizes document analysis and focus group discussions, divided into three stages: 1) analyzing strategies for student development, 2) examining the alignment of vision, identity, and student development strategies, and 3) formulating recommendations for student development strategies for schools under the Secondary Education Service Area Office Chiang Mai. The sources and participants include: 1) secondary data from the supervising agencies and 34 schools, and 2) a research team of three members. The tools used are: 1) a student development strategy analysis form, 2) a vision, identity, and strategy alignment analysis form, and 3) a focus group discussion record form. The statistics used are frequency, percentage, and content analysis. The research findings indicate that: 1) the key points of the student development strategies align with the National Education Standards B.E. 2561 and the Basic Education Standards, covering nine main areas. The most frequently addressed area is the development of morality, ethics, and desirable characteristics, while the least addressed is the promotion of citizenship among students. 2) School's student development strategies align most closely with their visions and least with their identities. 3) The recommendations for formulating student development strategies for schools under the Secondary Education Service Area Office Chiang Mai are: 3.1) schools should incorporate the key points outlined in the National Education Standards and Basic Education Standards into their student development strategies, and 3.2) schools should develop clear, concrete, and actionable student development strategies that align with and reflect their vision and student identity.